Self-esteem, social comparison, and interpersonal communication competence as predictors of students’ psychological well-being - Ismailova, Aruzhan; Naubayeva, Khapiza; Zheldibayeva, Raigul; Kontrimienė, Simona (Frontiers in Education, 2025)
BackgroundThe extent to which students’ psychological well-being is determined by their communication in society and self-appraisal, including comparisons to other individuals, has not been previously examined within a single model. Motivated by this literature gap, the present study sought to test a hypothetical model embodying self-esteem and perceived interpersonal communication competence as direct regressors of self-reported psychological well-being, with social comparison inclination reciprocally linked to the criterion.MethodsA cross-sectional, quantitative correlational design was implemented. Four well-recognized questionnaires were administered via an anonymous online survey to students across various undergraduate programs at a public university. The survey responses from 348 students aged 18.8 years on average (55.2% females) were subjected to a multiple linear regression analysis.ResultsThe results supported the proposed conceptual framework: both perceived communication competence and self-esteem positively predicted students’ mental well-being. Conversely, higher self-reported social comparison intensity was associated with reduced psychological well-being. All paths were statistically discernible.ConclusionThis investigation represents the first attempt to assess the relationship between one’s subjective communication competence and mental well-being per se, rather than its sub-components. The findings highlight that contemporary students, navigating a world of constant digital and face-to-face interactions, risk harming their mental well-being when their personal standards are strongly influenced by peers.